Mexican Americans and the Catholic Church, 1900-1965 - Dolan, Jay P. (University of Notre Dame Press, 1994)
Within the American Catholic Church the Mexican American legacy is the longest, as is their struggle for full acceptance in the institutional church. In this volume three historians examine religious history, focusing on Mexican American faith communities. Originally published in 1994.
Description based upon print version of record.
Keywords: Catholic Church -- United States -- History -- 20th century.; Église catholique -- Histoire -- 20e siècle.; Mexican American Catholics -- History.; Catholiques américains d'origine mexicaine -- Histoire.; RELIGION / Christianity / Catholic; Electronic books.